Analisi Tingkat Pendidikan dan Produk Domestik Regional Bruto terhadap Tingkat Pengangguran di Kota Makassar - Syamsu Nujum; Zainuddin Rahman; Hukma Purnama (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2020)
The objectives of this study are: 1) To Analyze the Effect of Education Level Partially on Unemployment in Makassar City, 2) To Analyze the Effect of Gross Regional Domestic Product Partially on Unemployment in Makassar City, and 3) To Analyze the Effect of Education Level and Gross Regional Domestic Product simultaneously against unemployment in Makassar City. The analytical method used in this study is multiple linear regression. The results showed that the level of education had no significant effect on the unemployment rate in Makassar City. Gross Regional Domestic Product did not significantly influence unemployment in Makassar city and together with the education level of funds the gross regional domestic product did not significantly influence unemployment in Makassar City.